Knowledge And Anxiety About The Immunization Effect On Motivation Of Mother Giving Full Basic Immunization - Amirudin.K.HI.Majid (Chakra Brahmanda Lentera Institute, 2020)
Understanding of mothers about immunization is very necessary because with high knowledge about immunization, it is expected that mothers want to fully immunize their children and not be afraid or anxious. Objective To find out the level of knowledge and anxiety about the effects of immunization on the motivation of mothers to provide complete basic immunization in the UPTD area of ​​Paleleh Health Center, Buol Regency. The design used in the study was cross sectional. Population is all mothers who have babies / toddlers. The sample size was 188 respondents using Purposive Sampling techniques. Independent variables of research are Knowledge and anxiety. The dependent variable is motivation. Data was collected using a questionnaire, then data were analyzed using the Spearman Rho test, with a significance level of α ≤ 0.05. The results showed that more than half of respondents had enough knowledge as many as 99 respondents (52.7%), had mild anxiety as many as 86 respondents (45.7%), had sufficient motivation as much as 82 respondents (43.6%). The results of the study with a <0.05 found that knowledge (p = 0,000) and anxiety (p = 0,000) on motivation with p <a, so it can be concluded that H1 is accepted and H0 is rejected which means that there is a relationship between Knowledge and Anxiety About Immunization Effects Against the Motivation of Mothers Giving Complete Basic Immunization in the UPTD Working Area of ​​Paleleh Health Center, Kab. The better motivation of the mother to do motivation can be influenced by good knowledge and the level of anxiety the mother has about immunization to be carried out